The Impact Of The Distribution Of Public Expenditure On Education Infrastructure Within The Syrian Governorates On Sustainable Economic Development - شرف سمير; صقر روان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aimed to study the relationship between public expenditure on education infrastructure in the Syrian governorates and achieving the requirements of sustainable economic development, due to the important impact of education on human capital, which is the basis of the economic development process, and for the development of countries all over the world. Time series data were collected for the study variables, which were represented by the annual change in the number of schools in each governorate as an independent variables and the composite sustainable economic development index as a dependent variable for the time period (1988-2019). It was subjected to a financial-statistical economic study that began with an analysis of the ratios, growth rates and components of these variables, followed by a study of the stability of time series, and finally, the long-term co-integration equations were estimated for public expenditure on education in the Syrian governorates using the ARDL model, the results of the study showed a long-term relationship between sustainable economic development and public expenditure on education infrastructure in the Syrian governorates, in addition to the study of the impact of the war on Syria by adding it as a dummy variable in the joint integration equation, where the researcher concluded that there is a negative impact of the war on Syria on development The sustainable economic situation through the negative impact of public expenditure on education infrastructure during these years.